KONTRIBUSI GURU PENJAS DALAM MENINGKATKAN KEDISIPLINAN SISWA - Maya Kurnia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract — The process of learning (education) is a process in which a person is taught to be faithful and obedient also his mind is nurtured and developed. Education for a developing nation like the Indonesian nation today is an absolute necessity that can not be negotiable, the development of education must also be in line with the development guidance step by step. A student in learning activities at school will not be separated from the various rules and regulations that apply in school, and every student is required to be able to behave in accordance with the rules and regulations that apply in school. However, for children who are unfamiliar with the discipline, this will become hard when done at school. This less disciplined child will usually violate the existing order because he thinks the rule is what he wants to do. This is where the necessary role of teachers to help improve students' learning discipline, which is also a tool to control the behavior of students who are considered still distorted so that students become discipline in terms of learning or others. Development with physical education in schools requires skills, such as basic movement skills, sports game techniques and strategies, internalization of values (sportsmanship, honesty, cooperation, etc.) and healthy lifestyle habits. Implementation is not through conventional teaching in the classroom that is theoretical study, but involves physical elements, mental, intellectual, emotional and social. Keywords — Physical Education, Discipline. Abstrak — Proses belajar (pendidikan) adalah proses yang dimana seseorang diajarkan untuk bersikap setia dan taat juga pikirannya dibina dan dikembangkan. Pendidikan bagi bangsa yang sedang berkembang seperti bangsa Indonesia saat ini merupakan kebutuhan mutlak yang tidak bisa ditawar lagi, perkembangan pendidikan juga harus sejalan dengan tuntunan pembangunan setahap demi setahap. Seorang siswa dalam mengikuti kegiatan belajar di sekolah tidak akan lepas dari berbagai peraturan dan tata tertib yang diberlakukan di sekolahnya, dan setiap siswa dituntut untuk dapat berperilaku sesuai dengan aturan dan tata tertib yang yang berlaku di sekolahnya. Akan tetapi bagi anak yang tidak terbiasa dengan tata tertib hal ini akan menjadi terasa berat ketika dilakukan pada saat di sekolah. Anak yang kurang disiplin ini biasanya akan melanggar tata tertib yang ada karena ia berpikir peraturan itu merupakan keinginan apa yang ia lakukan. Disinilah diperlukan adanya peran guru untuk membantu meningkatkan kedisiplinan belajar siswa, yang sekaligus menjadi alat pengendali perilaku siswa yang dianggap masih menyimpang sehingga siswa menjadi displin dalam hal belajar ataupun yang lainnya. Pengembangan dengan pendidikan jasmani disekolah membutuhkan ketrampilan, seperti ketrampilan gerak dasar, teknik dan strategi permainan olah raga, internalisasi nilai-nilai (sportifitas, jujur, kerjasama, dan lain-lain) serta pembiasaan pola hidup sehat. Pelaksanaannya bukan melalui pengajaran konvensional didalam kelas yang bersifat kajian teoritis, namun melibatkan unsure fisik, mental, intelektual, emosi dan sosial. Kata Kunci — Pendidikan Jasmani, kedisiplinan.